The Economic Effects of Anti‐Tampering Rules in Professional Sports Leagues. (15th June 2016) - Blair, Roger D.; Lopatka, John E.
Abstract : Every major North American professional sports league prohibits its members from 'tampering' with another member's employees. The prohibitions vary across leagues in content, scope, and enforcement, but at their core forbid clubs from soliciting another club's employees. Critically, the restrictions extend to discussions of employment that would commence only after a current employment contract ends. They therefore inhibit the flow of information about the demand for an employee's services. Professional sports leagues typically have monopsony power in labor markets. A no‐solicitation agreement among league members has the capacity to lower employees' wages. For players, whose contractual rights are traded, such an agreement need not affect the distribution of employees across clubs; for other employees, it may cause a misallocation of employees and therefore a deadweight loss. A no‐solicitation agreement may increase efficiency by enhancing the value of athletic competition, a product produced jointly by a sports league. But the argument that league anti‐tampering rules have this effect is weak. Copyright © 2016 John Wiley & Sons, Ltd.